Citizen e-participation in urban governance : crowdsourcing and collaborative creativity - Silva, Carlos Nunes (Advances in electronic government, digital divide, and regional development, 2013)
"This book explores the nature of the new challenges confronting citizens and local governments in the field of urban governance, exploring the role that Web 2.0 technologies play to promote citizen participation and empowerment in the city government"--Resumé vydavatele